Preface - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2012)
The present issue of the biennial journal, Focus: Papers in English Literary and Cultural Studies contains papers from the sixth conference of the Irish Society for Theatre Research. Hosted by the Department of English Literatures and Cultures of the Institute of English Studies and the Irish Studies Research Centre at the University of Pécs, the event took place on 29-30 April 2011.